774. Sexual Behaviors and Attitudes of Intimate Partners of Ebola Survivors. (31st December 2020) - Cunningham, Hannah M; Wohl, David; Tozay, Sam; Reeves, Edwina; Pewu, Korto; Johnson, Harrieta; Williams, Gerald; Conneh, Tonia; DeMarco, Jean; Fischer, William; Brown, Jerry
Abstract: Background: Sexual transmission of the Ebola virus (EBOV) from male survivors to their partners has been well-documented. While studies have characterized the sexual behaviors of male survivors of Ebola Virus Disease (EVD), there is little focus on their intimate partners. This study seeks to describe the attitudes and sexual behaviors of women who have had condomless sex with male survivors of the 2014-16 Ebola outbreak in Liberia, West Africa. Methods: Participants were recruited through voluntary referral by their sexual partners, all of whom were participants in a longitudinal EVD survivor cohort. From February to March 2020, 30 women (age range: 19-53 years) were enrolled and surveyed regarding their sexual behaviors with a focus on perceptions of risk for acquisition of Ebola from their partners and the measures taken to address this risk. Mix method quantitative and qualitative assessment of survey responses was completed. Content analysis was used to consider open-ended questionnaire responses. Results: Few women reported full compliance with the 2016 World Health Organization (WHO) recommendations for safer sex with EVD survivor partners, but 50% described utilization of a safer se x strategy to reduce risk of transmission. Major themes identified include: (1) an inaccurate perception of no or low risk of sexual transmission of Ebola virus, (2) negative attitudes towards condoms, (3) a preference for abstinence among those seeking to avoid infection, and (4) positive attitudes towards health care worker advice. Conclusions: Future outbreaks will benefit from intervention programs to address knowledge gaps among women and their male survivor partner regarding the risk of sexual transmission of Ebola and clear communication about effective strategies to reduce this risk. Disclosures: All Authors : No reported disclosures